Robert Carr, George Cartwright, and Samuel Maverick military order - Carr, Robert, active 1664.; Cartwright, George; Maverick, Samuel
Military order of Robert Carr, George Cartwright, and Samuel Maverick.
Collection material in English.
Forms part of: Miscellaneous Manuscripts collection.